2017
DOI: 10.1016/j.jaip.2016.06.025
|View full text |Cite
|
Sign up to set email alerts
|

Predictive Properties of the Asthma Control Test and Its Component Questions for Severe Asthma Exacerbations

Abstract: Background Current U.S. guidelines recommend the Asthma Control Test (ACT) for assessing disease control and selecting treatment. Objective The goal of this study was to prospectively assess the ACT and its component questions for their utility in predicting risk of severe asthma exacerbations. Methods Individuals were participants in the Study of Asthma Phenotypes and Pharmacogenomic Interactions by Race-ethnicity (SAPPHIRE), and those included in the current analysis had the following characteristics: ag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
14
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(15 citation statements)
references
References 32 publications
1
14
0
Order By: Relevance
“…Almost all of the 10 publications reporting on ACT score and rescue medication use [15][16][17][18][19][20][21][22][23][24] found a relationship between worsening ACT scores and increasing short-acting beta agonist (SABA) or rescue inhaler use (Table 1). Weak but statistically significant correlations between ACT score and the number of SABA inhalers dispensed were identified in two publications (ρ = − 0.33, p = 0.001 in both); these studies may have been reporting on the same population [15,16].…”
Section: Act Score and Rescue Medication Usementioning
confidence: 99%
See 2 more Smart Citations
“…Almost all of the 10 publications reporting on ACT score and rescue medication use [15][16][17][18][19][20][21][22][23][24] found a relationship between worsening ACT scores and increasing short-acting beta agonist (SABA) or rescue inhaler use (Table 1). Weak but statistically significant correlations between ACT score and the number of SABA inhalers dispensed were identified in two publications (ρ = − 0.33, p = 0.001 in both); these studies may have been reporting on the same population [15,16].…”
Section: Act Score and Rescue Medication Usementioning
confidence: 99%
“…Ten studies reported on the relationship between improvement in ACT score and reduction in asthma exacerbations (Table 1) [17,22,23,[26][27][28][29][30][31][32].…”
Section: Act Score and Asthma Exacerbationsmentioning
confidence: 99%
See 1 more Smart Citation
“…Average daily exposure to short acting beta agonist (SABA) medication was estimated using records of SABA fills in the 3-month period preceding study enrollment. Separate metrics of SABA use were calculated for nebulizer use and metered dose inhaler (MDI) use, as we have previously shown that both the form and the frequency of SABA medication use may be related to asthma severity [31,32]. Average daily SABA use for each participant was estimated by summing the total number of doses (e.g., 50 puffs per canister) dispensed for that individual in the 91 days preceding enrollment and dividing by 91.…”
Section: Medication Use and Asthma Severitymentioning
confidence: 99%
“…Among the five questions assessed in the ACT, there was no association between the frequency of reliever use and AEs within six months; although other four items on the ACT regarding symptom frequency and effect of asthma on daily living showed an association with exacerbations. Conversely, Cajigal et al [29] reported that rescue medication usage is the most sensitive question in predicting the risk of severe AEs within six months among patients with severe asthma, 30% of whom experienced severe AEs during the six-month study period. These studies suggest that the interpretation of individual questions in ACT for predicting the risk of AEs could be different among asthmatic patients with various severities of asthma and regional background because the usage of reliever medications could be dependent not only on their symptoms but also on individual difference in thresholds or experience.…”
Section: Discussionmentioning
confidence: 99%